Corporate governance mechanisms and financial performance of banks: Empirical evidence on the multi-theory perspective in corporate governance - Eriqat, Ibrahim O A; Tahir, Muhammad; Zulkafli, Abdul Hadi (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to examine the impact of corporate governance on the financial performance of banks in the MENA region. The study uses a sample of 37 banks listed on the stock exchanges of four countries in the MENA region, namely Jordan, Palestine, Qatar, and Kuwait, from 2016 to 2020. This study employed static panel estimation methods for analysis purposes. The main findings of this study show that board size, CEO duality, and transparency and disclosure have a positive effect on banks’ financial performance, while the presence of women directors on the board and insider ownership has a negative impact on banks’ financial performance. The findings of this study support the multi-theory perspective in corporate governance. Furthermore, it can help managers, regulators, and policymakers focus on the areas of corporate governance that improve banks’ financial performance.